2013
DOI: 10.1186/1756-3305-6-34
|View full text |Cite
|
Sign up to set email alerts
|

Induction of long-lasting protective immunity against Toxoplasma gondii in BALB/c mice by recombinant surface antigen 1 protein encapsulated in poly (lactide-co-glycolide) microparticles

Abstract: BackgroundCurrent development efforts of subunit vaccines against Toxoplasma gondii, the etiological agent of toxoplasmosis, have been focused mainly on tachyzoite surface antigen 1 (SAG1). Since microparticles made from poly (lactide-co-glycolide) (PLG) polymers have been developed as safe, potent adjuvants or delivery systems, we aimed to encapsulate recombinant SAG1 (rSAG1) with the PLG polymers to prepare PLG-encapsulated rSAG1 (PLG-rSAG1) microparticles that would sustain rSAG1 release and generate long-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 33 publications
3
85
0
Order By: Relevance
“…The protein is encapsulated in 50:50 poly(lactide-co-glycolide) microparticles using the double emulsion method as described previously [41,42], with minor modifications [22][23][24]. In the process, PLG polymer is first dissolved in an organic solvent.…”
Section: Encapsulation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The protein is encapsulated in 50:50 poly(lactide-co-glycolide) microparticles using the double emulsion method as described previously [41,42], with minor modifications [22][23][24]. In the process, PLG polymer is first dissolved in an organic solvent.…”
Section: Encapsulation Methodsmentioning
confidence: 99%
“…However, further improvements such as enhancement of protein load in PLG microparticles, as well as, optimization and stabilization of protein release are needed to evaluate the feasibility [40]. On the other hand, Western blotting assay with use of mouse monoclonal antibodies specific to tachyzoite SAGs demonstrated that released rSAG proteins from PLG microparticles still retained the original SAG antigenicity during the release from PLG microparticles [22][23][24]. These data indicate that both the encapsulation procedure and release from microparticles in our previous work are not detrimental to the antigenicity of …”
Section: Preparation Of Toxoplasma Sag-loaded Microparticlesmentioning
confidence: 99%
See 3 more Smart Citations